(untitled) (Acta Scientiarum. Biological Sciences, 2017)
Achatina fulica, known as Giant African Snail (GAS), was introduced in Brazil as a substitute for the European escargot, Helix aspersa maxima. However, its cultivation was abandoned and the mollusk became an invasive species, found throughout Brazil and causing damage to health and the environment. In this context, this study analyzed the knowledge of the population about the damage caused by GAS, seeking to reveal a regional scenario on this issue. This exploratory and cross-sectional study was conducted by means of a questionnaire applied to 150 people, which obtained sociodemographic characteristics of respondents and specific responses about the knowledge and handling of GAS. The results showed that most of the respondents know the snail and are concerned about the transmission of diseases and losses in agricultural crops, but few recognize this pest as the basis of environmental imbalance. It is suggested to implement actions seeking the dissemination of such knowledge and the awareness of the population about the impact of this mollusk on the environment.